Run-time Exchange of Mechatronic Controllers Using Partial Hardware Reconfiguration - Bobda, Christophe; et al. (Proceedings of the International Conference on Field Programmable Logic and Applications (FPL2003), 2003)
We present an efficient technique to implement multi-controller systems using partial reconfigurable hardware (FPGA). The control algorithm is implemented as a dedicated circuit. Partial runtime reconfiguration is used to increase the resource efficiency by keeping just the currently active controller modules on the FPGA while inactive controller modules are stored in an external memory. © Springer-Verlag Berlin Heidelberg 2003.
UnivIS-Import:2015-04-16:Pub.2003.tech.IMMD.inform.runtim